The Role of Mesostriatal Dopamine System and Corticostriatal Glutamatergic Transmission in Chronic Pain - Barbara Ziółkowska (Brain Sciences, 2021)
There is increasing recognition of the involvement of the nigrostriatal and mesolimbic dopamine systems in the modulation of chronic pain. The first part of the present article reviews the evidence indicating that dopamine exerts analgesic effects during persistent pain by stimulating the D2 receptors in the dorsal striatum and nucleus accumbens (NAc). Thereby, dopamine inhibits striatal output via the D2 receptor-expressing medium spiny neurons (D2-MSN). Dopaminergic neurotransmission in the mesostriatal pathways is hampered in chronic pain states and this alteration maintains and exacerbates pain. The second part of this article focuses on the glutamatergic inputs from the medial prefrontal cortex to the NAc, their activity changes in chronic pain, and their role in pain modulation. Finally, interactions between dopaminergic and glutamatergic inputs to the D2-MSN are considered in the context of persistent pain. Studies using novel techniques indicate that pain is regulated oppositely by two independent dopaminergic circuits linking separate parts of the ventral tegmental area and of the NAc, which also interact with distinct regions of the medial prefrontal cortex.